SEJARAH KESENIAN BORUDAH DI KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU 1980-2016 - Kurniawan, Maman; Isjoni, Isjoni; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Borudah art which is located in Kecamatan Rokan IV Koto is an art that contains religious values education which summarized in the form of Arabic poetry (poetry) and is sung with the rhythm of chronic melancholic musicality. Borudah art is often played by men with contain 6 to 8 members. This art is generally taken up at night during religious events such as the welcoming of Ramadhan holy month and the customs event. The poems that are played in this bourgeois art usually contain about shalawat or praise to the Prophet Muhammad SAW. Borudah art in general has several functions such as function at the wedding, religious functions, entertainment functions and beauty functions. Borudah art in the rokan IV koto rokan hulu district until now still able to maintain its existence in the middle of the wave of modernization. Various activities undertaken by the people of Rokan IV Koto District in preserving Borudah Arts such as Inviting Borbel art performers at the wedding ceremony, featuring Borfore Arts at the ceremony of welcoming the holy month of Ramadan and the Aqiqah event. Based on the data that can be broadly borzen art contains several values such as religious values, moral values, social values and customs values.Keywords: History, Borudah Art, Rokan IV Koto